Firms' willingness to pay local business tax: The impact of trust and public goods - Henning Giese; Vanessa Heinemann-Heile (Arbeitskreis Quantitative Steuerlehre (arqus), 2024)
This study analyzes whether and to what extent the provision of public goods and firms' trust in local governments' handling of local business tax revenues are associated with firms' willingness to pay local business tax. Using survey data on German small- and medium-sized firms, we find that the average perceived provision of public goods is not associated with the willingness to pay local business tax. Separating public goods into private- and business-related public goods, we find that the perception of public goods related to the private sphere of firms' decision-makers is associated with an increase in firms' willingness to pay local business tax by about 10%. However, public goods related to the business sphere show no similar association. Contradictory to the perceived provision of public goods, we find surprisingly no association between firms' willingness to pay local business tax and the actual provision of public goods. Trust in local governments' handling of tax revenue increases firms' willingness to pay local business tax significantly, with an effect size of about twice as large as for the perception of provided private-related public goods. These findings indicate that the handling of tax revenues exerts a more pronounced influence on firms' willingness to pay than the actual utilization of these revenues. Documenting tax revenue implications, we further show that the average willingness to pay local business tax within a local government is associated with a significant decrease in tax avoidance by about 10%. Our results inform local governments about how the provision of public goods and the building of trust can sustainably contribute to firms' willingness to pay local business tax. Thus, our results contribute to the understanding of how taxes can be efficiently collected and effectively used.
Keywords: H25; H26; H41; H71; D91; 330; Tax Perception; Business Taxation; Tax Avoidance; Public Goods; Tax Revenue